Analisis Harga Pokok Produksi Sebagai Dasar Penentuan Harga Jual Air Minum pada Perusahaan Umum Daerah (PERUMDA) Air Minum Muara Tirta Kota Gorontalo - Khairon Nur Annisa Laleno; Mahdalena (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the calculation of the selling price of drinking water at the Regional Public Company (PERUMDA) Muara Tirta Drinking Water, Gorontalo City. The data sources used in this research are primary data obtained directly from the Regional Public Company (PERUMDA) Muara Tirta Drinking Water, Gorontalo City and secondary data in the form of time series performance report data over a three year period, namely from 2020 to 2022. This research uses observation, interview and documentation methods by looking at company performance report documents. The data analysis technique used in this research is quantitative descriptive analysis, namely calculating the cost of production using the Full Costing method and selling price calculations using the Cost Plus Pricing method. The results of this research show that the calculation of the cost of production using the full costing method is fast and accurate as a basis for determining the selling price for each cubic meter of water produced at the Regional Public Company (PERUMDA) Muara Tirta Drinking Water, Gorontalo City. This research shows that the selling price of water from 2020 to 2022 is above the cost price, which indicates that the company is making a profit.